2015
DOI: 10.1007/s11629-013-2925-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land use change on runoff and sediment yield in Da River Basin of Hoa Binh province, Northwest Vietnam

Abstract: runoff disch Basin in th Water Asse model was observed m selected gau SWAT gene and sedim efficiency ( ratio (RSR) runoff, the v 0.02, and 3 0.01, and 1 For sedime value of N period were -2.56 durin results of status has a yield. Chan 2005 from contributed from 182.5 101.3 to 14 Effect Da Riv NGO T NGUY Rajend 1 Asian 2 Facult 3 Facult Citatio Basin of © Scie

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 21 publications
(16 reference statements)
2
35
0
Order By: Relevance
“…Similarly, [50] reported that an increase in annual surface runoff increased when forest lands were converted to urban areas and decreased during when forestland gained a significant expansion. Maalim et al [51] [53] partly play a role.…”
Section: Impact Of Land Use and Cover Change In The Murchison Bay Catmentioning
confidence: 98%
“…Similarly, [50] reported that an increase in annual surface runoff increased when forest lands were converted to urban areas and decreased during when forestland gained a significant expansion. Maalim et al [51] [53] partly play a role.…”
Section: Impact Of Land Use and Cover Change In The Murchison Bay Catmentioning
confidence: 98%
“…Sànchez et al (2002) conducted an experiment in the Venezuelan Andes showed that erosion in -1 the natural forest was 0.43 mg ha , which was lower than -1 horticultural crops in rotation (22 mg ha ), apple tree (1.96 -1 -1 mg ha ), and pasture without grazing (1.11 mg ha ). Ngo et al (2015) reported that land use change in Da River Basin in Vietnam from forest to field crop and urban area increased annual runoff and sediment, while forest expansion conservation decreased runoff and sediment. Table 2 and Tabel 3 show soil moisture dynamic in the forest, agroforestry, and rainfed agriculture at upper, middle, and downstream for dry season (August to October 2014) and rainy season (November 2014−March 2015), and for two soil depths, namely 0−20 cm and 20−40 cm.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency and intensity of the rainfall are concentrated over a short period where rainstorms and super rainstorms are major contributions to the landslide hazard in the area [23]. Generally, average precipitation ranges from 1520-2255 mm per year [24].…”
Section: Study Sitementioning
confidence: 99%